The Development of Connected Learning Modules in Computer Systems and Microprocessor Electronics Subjects at 10th Grade in Vocational High School - Hasbial, Yanda Mochamad; Mukhidin, Mukhidin; Budi, Agus Heri Setya (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Learning modules are one of the important things in the continuity of learning. The learning modules are arranged systematically and cover all the content of the learning material that will be delivered by including an evaluation at the end of the module section to determine students' ability to understand learning. This study aimsto determine the effective development of connected learning modules in 10th grade at VHS (Vocational High School). The data collected is in the form of the feasibility of developing learning modules. This research is field research with the descriptive qualitative method. MAXQDA is used to explain the mapping of the research results obtained. The research subject involved the teacher as MGMP Team (Subject Teacher Conference) in this VHS, which provides an assessment through a validation sheet regarding the feasibility of the module to be used in the learning process. The results of this study indicate that the module that will be used already has a good and proper category as a support for the Connected Learning model to be applied learning process in the classroom. The conclusion based on the study results shows that the Connected Learning model can be used as an alternative learning model that only focuses on conventional learning models. This study’s results imply that the Connected Learning model can make it easier for teachers to be effective in the learning process.